Discourse Analysis Of Shopee Advertising "Cod Cek Dulu" - Ronny Yudhi Septa Priana; Husnan Nurjuman; Tri Djoko Sulistiyo (Jurnal Multidisiplin Sahombu, 2024)
This research aims to reveal the meaning of the message in the Shopee advertisement "COD Cek Dulu" using Teun A. Van Dijk's discourse analysis model. This research uses a content analysis approach to advertising content discourse with this research data in the form of pieces of Shoppe advertisements "COD Cek Dulu". The research results show that the advertisement uses a complete advertising discourse structure in the form of a Superstructure consisting of headline, illustration, body copy and signature. Micro structure consists of words, sentence choices and language style and macro structure consisted of the meaning and message conveyed. Shopee's advertising discourse "COD Cek Dulu" aims to inform and persuade consumers about new programs and services from Shopee while improving consumer image and trust